Learning as an explanation of export development (Revista de Administração, 2011)
This article aims to analyze the mechanisms that trigger and maintain durable exporting pathways. By using the pathway notion, its major contribution lies in discussing how learning can be viewed as an explanatory factor of the development of exporting. Empirically supported by a qualitative, longitudinal case study, the authors analyze the permanence-continuity of the exports of two footwear manufacturers from 1970 to 2005. The results show that the permanence-continuity of exporting is related to a confluence of causes, which express a cycle of events-reflections that provide feedback to each other, thereby triggering the permanence-continuity of the pathway. From a theoretical standpoint, these results suggest that the development of exports is a complex, non-linear phenomenon, a conclusion that runs contrary to the mainstream literature on exporting.